An Educational Application of Distributed Measurement Systems - J. Saliga (Radioengineering, 1999)
This paper describes an educational application of distributed measurement systems for the tutored and self-educational process that has been designed and applied at the Department of Electronics and Multimedial Telecommunications, Technical University of Kosice for students at the senior level of their study. The main goal of this activity has been to improve and spread our students' knowledge beyond the traditional university education in the area of measurement and communications. The students involved do not only play a passive role in the usage of a ready-made distributed measurement system by executing a remote measurement but they have the opportunity to participate in the process of design, carrying out and supervising an own simple distributed measurement system. To simplify their task, they may either use the graphical programming environment LabVIEW or the standard ANSI C language based on the programming environment Labwindows/CVI with ready-made instrument drivers (GPIB, serial and plug-in multifunction boards) and basic software skeletons. The overview of the students' resources, task-solving steps and goals as well as the present results, experience and the expected future extensions are presented, too.